PELESAPAN PREPOSISI DALAM GRAMATIKA BAHASA INDONESIA - Fransiskus Xaverius Sawardi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2017)
This paper is based on the use of effective sentence-making rules in Indonesian language teaching which reads: subject and object should not be given a preposition. Sentences whose subject is preceded by a preposition are deemed ineffective / ungrammatical. Onthe other hand, the preposition is obligatory to express the role of locative, instrument, comitative, etc.. Under certain conditions the preposition is optional. For example, in the sentence Anjing itu dipukul (oleh) Ali. The problem are: (i) what is the preposition function in Indonesian grammar? (ii) at what position can the preposition be deleted? (iii) why are these prepositions be deleted? To answer the problem, the clause will be analyzed from the predicate and argument base. Arguments are distinguished from nonargument. Prepositions in the Indonesian language are used to distinguish arguments and non arguments, and determine the role of semantic constituent clauses. Prepositions may be fixed in (i) positions behind the direct verb, and (ii) the semantic role is obvious. The reason for this clear semantic role that makes the preposition can be wiped out.